Russian version of BRIEF2 Teacher Forms: validation study in typically developing children aged 5 to 7 years old - Gavrilova, Margarita; Aslanova, Margarita; Tarasova, Kristina; Zinchenko, Yuri (Frontiers in Psychology, 2023)
This study aimed to examine the psychometric properties of the Russian version of the Behavioral Rating Inventory of Executive Function®, Second Edition (BRIEF2) Teacher Forms and investigate its dimensional structure. The sample consisted of 178 typically developing children aged 5 to 7 years. Internal reliability analysis indicated high reliability (from 0.87 to 0.95) for the three composite indices and the Global Executive Composite across all age groups. Confirmatory factor analysis revealed that the dimensional structure of the Russian version of BRIEF2 was different among children aged 5 and 6 years compared to children aged 7 years, which is probably because, in Russia, the transition from kindergarten to school takes place upon reaching the age of 7. The results confirm that the Russian version of the BRIEF2 Teacher Form can be used as a valid tool to assess EF in 5- and 6-year-old children, provided that the three BRIEF2 indices are used for clinical interpretation. For 7-year-old children, the BRIEF2 was found to be an insufficiently valid tool to assess executive function.